(untitled) (Intent Research Scientific Journal, 2024)
This article delves into the dynamic landscape of English language teaching, exploring the role and significance of both traditional and modern interactive methods. The study investigates the impact of these methods on student engagement, language acquisition, and overall learning outcomes. By analyzing existing literature and presenting a detailed discussion, this article aims to provide valuable insights for educators seeking to optimize their teaching approaches.